Genetic diversity of bulbus Fritillariae Thunbergii Miq. varieties based on ISSR markers - LIU Xiao-xian; CHEN Chuan; PAN Lan-lan; CHEN Yu-hua; FU Cheng-xin (浙江大学学报. 农业与生命科学版, 2010)
The genetic diversity of Fritillaria thunbergii Miq. distributed in Pan an and the other areas was investigated and their population structure was inferred by inter-simple sequence repeats (ISSR) techniques. Populations of F. thunbergii var. chekiangensis and two horticultural species (Daye & Duozi) were included, and F. przewalskii and F. anhuiensis were introduced as the outgroup. Based on results of ISSR analysis, F. thunbergii could be classified into two major groups. One included the samples from Pan an in Zhejiang Province, while samples of the other group were not from the above area. Low levels of genetic diversity were observed in all seven populations of F. thunbergii (Ao=1.03-1.16, Ae=1.03-1.10, He=0.01-0.06, Ho=0.02-0.09, PPB=3.45% -15.86%), which were lower than that of other fritillary populations. UPGMA dendrogram based on Nei's genetic distance showed that F. thunbergii var. chekiangensis was a variation of F. thunbergii. It may be a product of artificial selection during herbs cultivate. F. thunbergii (Daye) was quite same as F. thunbergii, while F. thunbergii (Duozi) had differentiated in molecular level, presuming that F. thunbergii (Duozi) may be a production of hybridization.